Analisis Produktivitas dan Karakteristik Human Capital PT Pertamina (Persero) Periode 2020-2024 - Faldy Herdian (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Human capital has become a strategic asset that determines organizational productivity and competitiveness. This study aims to analyze the productivity and characteristics of human capital at PT Pertamina (Persero) during the 2020–2024 period. A descriptive quantitative approach was employed using secondary data obtained from the company's Annual Reports and Sustainability Reports. Human capital productivity was measured using Revenue per Employee, EBITDA per Employee, and Asset per Employee, while human capital characteristics were analyzed based on the number of employees and educational composition. The results indicate that all productivity indicators fluctuated throughout the observation period, influenced by changes in financial performance and workforce size. Meanwhile, the educational profile of employees improved, as reflected by the increasing proportion of employees holding undergraduate and postgraduate degrees. These findings suggest that improving human capital quality should be accompanied by effective workforce management to optimize organizational productivity and support sustainable corporate performance.